Assessing the Implementation of First-Party Professional Certification (LSP-P1) Via Industry Collaboration: An Employability Strategy for Motorcycle Automotive TVET Graduates in West Java - Muhamad Kamaludin; Yadi Hikmah Setiana; Tatang Mulyana (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims are (1) evaluate the implementation of the UKK of the LSP-P1 certification scheme in Vocational High Schools, (2) determine the involvement of industry in the UKK implementation process, (3) determine the impact of collaboration between Vocational High Schools and industry in the implementation of UKK on increasing the employability of TVET graduates, so that strategic recommendations are generated for Vocational High Schools, LSP-P1, and industry in increasing the effectiveness of UKK implementation and increasing the employability of TVET graduates. This study uses an evaluation research method using the CIPP model, a descriptive evaluative approach that incorporates survey techniques and in-depth interviews. Respondents include the head of the expertise program, the head of the TUK, LSP-P1 assessors, representatives of partner industries, and alumni who have participated in the UKK. Data are analyzed quantitatively and qualitatively. This study was conducted in West Java at six TBSM Vocational High Schools. The results show that the LSP-P1 UKK is relevant to the needs of the automotive industry, but is not fully adaptive to the development of EV technology. Assessors and test materials are quite appropriate, but modern facilities and competency updates are still obstacles. The implementation process meets standards, but external oversight from the industry needs to be strengthened. Certified graduates have higher employability than non-certified graduates, but their readiness for new technologies remains limited. Therefore, the UKK (LSP-P1) certification scheme has proven effective in increasing the competitiveness of TBSM vocational high school graduates in West Java. However, it requires curriculum innovation, strengthening of facilities, and more intensive involvement from industry at every stage of implementation, including assessor criteria, competency test materials, assessment standards, and recognition of competency certificates.